PENGALAMAN PSIKOLOGIS INDIVIDU DENGAN THALASEMIA - , Rr. Diyah Woro Dwi Lestari, Subandi, M.A, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Chronic disease has different effect on individuals who living with. Livneh and Antonak (2005) states there are problems such as individuals with chronic disease conditions that increase stress, psychosocial crisis, grief, reduced function in life, self-image changes due to disease or treatment, changes in self-concept, stigma and prejudice in society, the coping of the uncertainty of health conditions in the future and changes in quality of life. Reduction of the negative impact inidilakukan one of them by understanding the condition and seek the meaning behind the pain experience the pain and things that can reduce the psychological impact of the disease (Taylor, 1995